Pengaruh Media Puzzle Education Game terhadap Perkembangan Kognitif dan Bahasa Anak TK - Zusanty, Mery; Masitoh, Siti; Setyowati, Sri (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this study was to test the Puzzle education game on children's cognitive and language abilities. To see the effect of Puzzle media, researchers used a quasi-experimental method; nonquivalent control group design. The research subjects were children of Group B, Group I in Bandung District. Data collection using observation, portfolio. The conclusion from the analysis is that there is an influence of Puzzle education media on the cognitive and language abilities of children in Group B of Cluster 1 in Bandung District, Tulungagung Regency. With educational Puzzle game media, cognitive and language development is better than using magazines or children's worksheets. Keywords: Media Puzzle Education Game, Cognitive Development, Language Development